1993
DOI: 10.1002/art.1780360904
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of naproxen and acetaminophen in a two‐year study of treatment of osteoarthritis of the knee

Abstract: The efficacy of ACT treatment and NPX treatment was similar, although it was slightly better for NPX. The toxicity rate was slightly lower with ACT. However, the high rate of withdrawal in both treatment groups suggests that neither is satisfactory for the treatment of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0
12

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(113 citation statements)
references
References 24 publications
3
98
0
12
Order By: Relevance
“…In studies on which the ACR guidelines were based, dosages over 2,600 mg/day were not included (32), while other studies that did investigate higher doses (4,000 mg/day) demonstrated similar levels of subjective symptoms of gastric discomfort between ketoprofen and acetaminophen (10) and similar adverse events between ibuprofen and acetaminophen (18). Several randomized controlled trials and epidemiologic studies have demonstrated an increase in rates of dyspepsia in patients who took acetaminophen (15,17), and some epidemiologic studies showed a significant association between acetaminophen intake and gastric ulcers (14,33).…”
Section: Discussionmentioning
confidence: 99%
“…In studies on which the ACR guidelines were based, dosages over 2,600 mg/day were not included (32), while other studies that did investigate higher doses (4,000 mg/day) demonstrated similar levels of subjective symptoms of gastric discomfort between ketoprofen and acetaminophen (10) and similar adverse events between ibuprofen and acetaminophen (18). Several randomized controlled trials and epidemiologic studies have demonstrated an increase in rates of dyspepsia in patients who took acetaminophen (15,17), and some epidemiologic studies showed a significant association between acetaminophen intake and gastric ulcers (14,33).…”
Section: Discussionmentioning
confidence: 99%
“…Initially it was designed to measure walking function in patients with musculoskeletal disorders including osteoarthritis (27,28), rheumatoid arthritis (29,30), low back pain (31,32), and geriatric (aging) conditions (33,34). In these circumstances, factors such as joint swelling, stiffness, and inflammation effect walking speed.…”
Section: -Foot Walk Testmentioning
confidence: 99%
“…Like other timed distance tests, patients must be able to complete the 50-foot distance in order to participate in the test. Normative data exist in the literature for osteoarthritis and rheumatoid arthritis (27)(28)(29)(30).…”
Section: -Foot Walk Testmentioning
confidence: 99%
“…17,18 However, it can be seen from the Oxford League Table that overall, NSAIDs are clearly more efficacious than acetaminophen. A recent survey of 1799 patients with osteoarthritis found that the majority (>60%) preferred NSAIDs over acetaminophen in the symptomatic treatment of osteoarthritis based on perceived better efficacy.…”
Section: Comparison Of the Efficacy Of Nsaids With Other Analgesicsmentioning
confidence: 99%